2012
DOI: 10.1124/jpet.112.192146
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mouse Models Resistant to Diet-Induced Metabolic Disease: Is Energy Balance the Key?: Fig. 1.

Abstract: The prevalence and economic burden of obesity and type 2 diabetes is a driving force for the discovery of molecular targets to improve insulin sensitivity and glycemic control. Here, we review several transgenic mouse models that identify promising targets, ranging from proteins involved in the insulin signaling pathway, alterations of genes affecting energy metabolism, and transcriptional metabolic regulators. Despite the diverse endpoints in each model, a common thread that emerges is the necessity for maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…For example, the POLG mutator mice exhibit significant losses in oxidative capacity related to the loss of a mitochondrial DNA proofreading enzyme, but remained protected from the deleterious effects of an HFD because of higher glycolytic capacities (22). A recent review of the literature found several examples of mouse models that demonstrated metabolic protection from an HFD (23), with many of the mouse models that demonstrated metabolic protection exhibiting decreases in mitochondrial respiration. Altogether, this suggests that, temporarily, an animal can adapt to exposure to nutrient overload by altering the metabolic (i.e., glycolytic) phenotype of the skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the POLG mutator mice exhibit significant losses in oxidative capacity related to the loss of a mitochondrial DNA proofreading enzyme, but remained protected from the deleterious effects of an HFD because of higher glycolytic capacities (22). A recent review of the literature found several examples of mouse models that demonstrated metabolic protection from an HFD (23), with many of the mouse models that demonstrated metabolic protection exhibiting decreases in mitochondrial respiration. Altogether, this suggests that, temporarily, an animal can adapt to exposure to nutrient overload by altering the metabolic (i.e., glycolytic) phenotype of the skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Also requiring study is why some obese people remain insulin sensitive, whereas the majority of them are insulin resistant. In addition to the possibilities already discussed, such factors as alterations in capillary density and permeability (136,137), differences in collagen VI deposition (53,138,139), the release of LPS from bacteria by the gut microbiome (140)(141)(142), alterations of lipid droplet proteins such as FSP27 (CIDEC) that regulate the rates of lipid deposition and lipolysis in adipose tissue (19,143), and events that cause an imbalance between nutrient load and mitochondrial function (144), need to be considered. With respect to the microbiome, AMPK activity is significantly increased in tissues of germfree mice (145) and in mice treated with antibiotics (146), suggesting that AMPK suppression by factors released by bacteria of the gastrointestinal tract or other sites may be a normal occurrence.…”
Section: Figurementioning
confidence: 99%
“…When intentionally overfed, participants failed to compensate by raising voluntary activity (11). This failure of a “push mechanism” by energy intake also applies to cellular bioenergetics, because energy expenditure in all cells is not directly coupled to energy supply but rather is determined by the rate of energy turnover (pull mechanism) (53). Hence, increased energy turnover was identified as a common underlying protective mechanism in various genetic models resistant to diet‐induced metabolic disease (53‐56).…”
Section: Impact Of Energy Turnover On Energy Partitioning and Metabolic Healthmentioning
confidence: 99%